EVALUATION AND REGULATORY STATUS OF THE BANNED COMBINATION OF PCM & ACECLOFENAC - Inderpal singh; Dilpreet kaur; Ishan sahore; Manpreet kaur; Prabhjot singh; Sushant mehra (IJRDO-Journal of Applied Science, 2025)
The fixed-dose combination (FDC) of Paracetamol (PCM) and Aceclofenac has beewn widely used for pain and inflammatory conditions. However, scientific evaluation has raised concerns regarding its safety, pharmacological redundancy, and risk of adverse effects. Studies indicate that combining PCM with Aceclofenac offers no significant therapeutic advantage over individual drugs. Moreover, the combination increases the risk of hepatotoxicity and gastrointestinal complications. Regulatory bodies in India, including the Drugs Technical Advisory Board (DTAB), reviewed its risk–benefit profile. Based on evidence, the Government of India banned this FDC citing lack of rationality and heightened safety risks. The ban aligns with global regulatory standards emphasizing rational drug therapy. This evaluation highlights the importance of scientific scrutiny for FDCs to ensure public health safety